A lightweight thermal insulation ceramic material and a preparation method thereof
By using components such as kaolin, feldspar and spray drying bidirectional pressing process, lightweight thermally insulated ceramic materials are prepared, solving the problems of complex production processes, high cost and difficult performance optimization of existing materials, and achieving comprehensive performance with low thermal conductivity, high compressive strength and economical and environmental protection.
Patent Information
- Application Number
- CN202510027918.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing lightweight thermally insulated ceramic materials have challenges in complex production processes, high costs and difficult performance optimization, and the high temperature heating process consumes huge energy, which limits its energy-saving production and large-scale applications.
Lightweight thermally insulated ceramic materials are prepared by spray drying and bidirectional pressing processes to optimize the pore structure and mechanical properties of the pore structure and mechanical properties.
It achieves low thermal conductivity (minimum 0.12 W/m·K), high compressive strength (maximum 15.6 MPa) and economic and environmental protection of the material, significantly improving the thermal insulation and mechanical properties, and is suitable for large-scale industrial production.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic products, and in particular relates to a lightweight heat-insulating ceramic material and a preparation method thereof. Background Art
[0002] Lightweight insulating ceramic materials, with their unique physical and chemical properties, have shown broad application potential in the fields of heating plates and electric ceramic stoves. Such materials usually have low density and low thermal conductivity, as well as excellent high-temperature stability and mechanical strength. They can not only improve the thermal efficiency of the equipment, but also significantly reduce heat loss, thus helping to save energy and reduce emissions. In these application directions, lightweight insulating ceramic materials can effectively optimize the thermal conductivity of the heating plate and improve heating uniformity, thereby meeting the needs of modern home appliances for efficiency, safety, and environmental protection. However, the lightweight insulating ceramic materials currently used for heating plates and electric ceramic stoves still face many technical challenges in research and development and practical applications, such as complex production processes, high costs, and difficulty in performance optimization.
[0003] The production of traditional lightweight ceramics relies on high-purity raw materials such as kaolin, perlite, rare earths, and rare earth oxides, and is produced through casting, injection molding, or high-temperature sintering technology. These materials can maintain a low thermal conductivity at high temperatures while having a certain mechanical strength. However, due to the huge energy consumption during the heating process and the strict requirements on kiln equipment, they are limited in practical applications. For example, some traditional processes require baking at a high temperature of more than 1500°C for several hours, resulting in high equipment and production costs. In addition, the procurement cost of high-purity raw materials and their processing links further increase the overall production cost of the materials.
[0004] In recent years, with the development of advanced material technology and the promotion of green and low-carbon concepts, new lightweight thermal insulation ceramic materials have made certain breakthroughs in preparation technology and material systems. For example, low-temperature sintering technology significantly reduces the sintering temperature, and the material can be formed within the range of 700-1200°C. At the same time, by introducing industrial by-products such as fly ash, construction waste, and ceramic polishing slag as raw materials, it not only reduces production costs, but also realizes resource recycling and reduces the impact on the environment. The application of these technologies is not only of positive significance for promoting the low cost and greening of lightweight thermal insulation ceramic materials in the field of heating plates and electric ceramic stoves, but also provides important support for the sustainable development of the home appliance industry.
[0005] Taking the Chinese invention patent with publication number CN108129131A as an example, this technology proposes a low-temperature sintering method for replacing lightweight preheated ceramics using construction and other industries. By adjusting the type and amount of the agent and controlling the heating rate and insulation time during the firing process, the porous structure and performance of the material can be precisely controlled, with the characteristics of low density, controllable pore size, and low thermal conductivity. This method is simple in process, green and environmentally friendly, and suitable for large-scale industrial production. However, the compressive strength of some products is low, and it is difficult to meet the requirements of high-strength applications; when using a building foaming agent, the pore distribution of the product is affected by the process control, which may lead to uneven pores, thereby affecting the stability of the thermal insulation performance; some embodiments show that the water absorption rate exceeds 15%, which may lead to a decrease in long-term performance in a humid environment.
[0006] Another Chinese invention patent with announcement number CN105174905B uses rare earth oxides and negative ion powders as additives to optimize the thermal conductivity and environmental performance of the material. Although the heating temperature is comparable, the lightweight thermal insulation ceramic products prepared by this technology have excellent thermal insulation and health and environmental performance through scientific raw material ratios and processing procedures, providing the possibility for application. However, during the production process, it is necessary to pre-sinter at 850-1000℃ for 2.5-3.5h, and then keep warm at 1500-1650℃ for 7-8h. This high-temperature heating process has huge evaporation, which is not conducive to energy-saving production; rare earth oxides (such as lanthanum oxide, cerium oxide, etc.) and negative ion powders (such as tourmaline powder, opal powder, etc.) are used in the raw materials. These materials are relatively expensive, which increases the production cost and limits their large-scale application; the production process is complicated, including multiple grinding, molding, drying, cleaning, glazing and step-by-step sintering, with many process steps and precise control, which is not conducive to simple industrial operation.
[0007] Therefore, it is necessary to further improve the raw materials and production processes of lightweight thermal insulating ceramic materials in order to enhance the performance of lightweight thermal insulating ceramic materials while reducing production costs. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention provides a lightweight thermal insulation ceramic material and a preparation method thereof.
[0009] A lightweight thermal insulation ceramic material, composed of the following components by weight:
[0010] Kaolin: 30-40 parts;
[0011] Feldspar: 30-40 parts;
[0012] Hollow ceramic microspheres: 10-15 parts;
[0013] Alumina: 8-10 parts;
[0014] Composite foaming agent: 5-8 parts;
[0015] Nucleating agent: 0.5-1 part;
[0016] Silicone wettability additive: 0.5-1 part;
[0017] Coral mucus: 1-2 parts;
[0018] Polyammonium carbonate: 0.5-1 part.
[0019] Preferably, the melting point of the hollow ceramic microspheres is 1300-1400°C.
[0020] Preferably, the composite foaming agent is a mixture of CaCO3 and SiC in a mass ratio of 3:(1-2), and has a particle size of 5-10 microns.
[0021] Preferably, the nucleating agent is at least one of titanium dioxide and silicon oxide; further preferably, the nucleating agent is silicon oxide with a particle size of 5-10 microns.
[0022] The silicon wettability aid is at least one of sodium silicate, γ-aminopropyltriethoxysilane and methyltrimethoxysilane.
[0023] The present invention also provides a method for preparing a lightweight thermal insulation ceramic material, comprising the following steps:
[0024] (1) By weight, kaolin, feldspar and alumina powder are sieved through a 100-mesh sieve to remove large impurities, and then 30-40 parts of the sieved kaolin, 30-40 parts of the sieved feldspar, 8-10 parts of the sieved alumina powder, 10-15 parts of hollow ceramic microspheres, 5-8 parts of a composite foaming agent, 0.5-1 part of a nucleating agent, 0.5-1 part of a silicon wettability aid, 1-2 parts of coral mucus, and 0.5-1 part of polyammonium carbonate are mixed, and 10-15 parts of water are added, and the mixture is ball-milled at a speed of 300-400 r / min for 3-5 hours to obtain a homogeneous slurry, and finally granulated by spray drying to control the particle diameter to 1-3 mm;
[0025] (2) Pressing the particles obtained by spray drying in step (1) into a green body by a bidirectional pressing process at a pressure of 20-50 MPa; heating the green body in a drying furnace at 80-100° C. for 8-12 hours to remove moisture and stabilize the shape of the green body, thereby obtaining a dried green body; pre-sintering the dried green body at 700-900° C. for 2-3 hours, and then heating the green body from 700-900° C. to 1200-1300° C. at a heating rate of 10-20° C. / min to avoid bubble collapse or excessive expansion; maintaining the temperature at 1200-1300° C. for 4-6 hours to complete matrix densification and pore structure stabilization; and finally cooling the green body to room temperature at a rate of 5-10° C. / min to avoid cracking of the green body due to thermal shock, thereby obtaining the lightweight thermal insulating ceramic material.
[0026] The spray drying parameters of step (1) are: air inlet temperature: 180-200°C; air outlet temperature: 100-120°C; atomization pressure: 2-3 MPa; nozzle diameter: 1-1.5 mm.
[0027] The functions of the raw materials of each component of the present invention are:
[0028] Kaolin: provides basic support and ensures high temperature resistance;
[0029] Feldspar: It has natural sintering function and can reduce the sintering temperature;
[0030] Hollow ceramic microspheres: reduce density and enhance thermal insulation performance;
[0031] Alumina: Improves the mechanical strength and thermal shock resistance of materials;
[0032] CaCO3 releases CO2 at 700-900℃; SiC reacts at higher temperatures to release CO, prolonging the bubble time;
[0033] Nucleating agent: provides uniform nucleation sites to prevent the formation of large bubbles;
[0034] Silicone wettability additive: improves the wettability of the interface between bubbles and substrate and stabilizes the bubble structure;
[0035] Coral mucus: Increases matrix viscosity, inhibits bubble rise rate, and works synergistically with silicone wettability additives to improve the fluidity and formability of the slurry and make the pore structure more uniform;
[0036] Polyammonium carbonate: ensures uniform distribution of raw materials and foaming agents.
[0037] The thermal conductivity of the lightweight thermal insulation ceramic material prepared by the present invention reaches a minimum of 0.12 W / m·K, which is significantly lower than that of conventional thermal insulation ceramics. This is due to the use of composite foaming agents (CaCO3, SiC). The two-stage decomposition process generates evenly distributed small pores with a tight pore structure and no large pore aggregation, which effectively hinders the conduction of heat. The addition of nucleating agents (such as silicon oxide) further optimizes the distribution of bubbles, enhances the uniformity and closed porosity of pores, and reduces the overall thermal conductivity of the material.
[0038] The compressive strength of the lightweight thermal insulation ceramic material prepared by the present invention reaches 15.6 MPa, which is higher than that of the comparative example. This is mainly due to the synergistic effect of the composite foaming agent and the nucleating agent, which makes the pore structure more evenly distributed and the pore wall thickness moderate, thereby dispersing the external load. At the same time, the coral mucus and the silicon wettability additive synergistically improve the fluidity and formability of the slurry, reduce the microcracks of the green body, and improve the stability of the overall structure.
[0039] Spray drying technology ensures the uniformity of particles, improves the density and performance stability of the green body, and facilitates industrial production.
[0040] In summary, the lightweight thermal insulation ceramic material of the present invention exhibits excellent comprehensive performance in terms of thermal insulation performance, mechanical properties, and economic and environmental protection.
[0041] Beneficial effects of the present invention:
[0042] The present invention adopts CaCO3 and SiC as composite foaming agents, and a two-stage decomposition process generates evenly distributed small pores. The pore structure is tight and there is no large pore aggregation, which effectively hinders the conduction of heat. At the same time, with the cooperation of nucleating agent, coral mucus and silicon wettability additive, the uniformity of the pores is further enhanced, and the stability of the overall structure is improved, thereby obtaining a lightweight insulating ceramic material with both mechanical properties and thermal insulation properties. DETAILED DESCRIPTION
[0043] Kaolin, item number: GLT-K8U7, Lingshou County Juncai Mineral Products Processing Plant.
[0044] Feldspar, item number: sl-02, Lingshou County Shuolong Mineral Products Processing Plant.
[0045] The particle size of CaCO3 and SiC is 5-10 microns.
[0046] Hollow ceramic microspheres, item number: 07, particle size: 200-400 mesh, Gongyi Jinliang Refractory Materials Co., Ltd.
[0047] The particle size of silicon oxide is 5-10 microns.
[0048] The method for extracting coral mucus described in the embodiments and comparative examples comprises the following steps:
[0049] Take a 300cm 2 A living coral is taken, a 1 kg weight is freely dropped from 25 cm above the living coral twice to stimulate the living coral, and then the stimulated living coral is immersed in seawater for 80 minutes, and finally taken out and inverted to collect mucus, the obtained mucus and activated carbon particles are mixed at a mass ratio of 1:0.05, stirred at a speed of 120 r / min for 8 minutes, and the activated carbon is separated by centrifugation to obtain the coral mucus; the coral is a giant synophyllous coral in the waters of Sanya, Hainan.
[0050] Example 1
[0051] A lightweight thermal insulation ceramic material, composed of the following components by weight:
[0052] Kaolin: 35 parts;
[0053] Feldspar: 35 parts;
[0054] Hollow ceramic microspheres: 12 parts;
[0055] Alumina: 9 parts;
[0056] Composite foaming agent: 6 parts;
[0057] Nucleating agent: 0.8 parts;
[0058] Silicone wettability additive: 0.8 parts;
[0059] Coral mucus: 1.6 parts;
[0060] Polyammonium carbonate: 0.7 parts.
[0061] The composite foaming agent is prepared by mixing CaCO3 and SiC in a mass ratio of 3:2.
[0062] The nucleating agent is silicon oxide.
[0063] The silicon wettability aid is γ-aminopropyltriethoxysilane.
[0064] The present invention also provides a method for preparing a lightweight thermal insulation ceramic material, comprising the following steps:
[0065] (1) By weight, kaolin, feldspar and alumina powder were sieved through a 100-mesh sieve to remove large impurities. Then, 35 parts of the sieved kaolin, 35 parts of the sieved feldspar, 9 parts of the sieved alumina powder, 12 parts of hollow ceramic microspheres, 6 parts of a composite foaming agent, 0.8 parts of a nucleating agent, 0.8 parts of a silicon wettability aid, 1.6 parts of coral mucus and 0.7 parts of polyammonium carbonate were mixed, and 13 parts of water were added. The mixture was ball-milled at a speed of 400 r / min for 4 h to obtain a homogeneous slurry. Finally, the granulation was performed by spray drying to control the particle diameter to 2 mm.
[0066] (2) Pressing the particles obtained by spray drying in step (1) into a green body by a bidirectional pressing process at a pressure of 40 MPa; heating the green body at 90° C. for 10 h in a drying furnace to obtain a dried green body; pre-sintering the dried green body at 800° C. for 2.5 h, then heating the green body from 900° C. to 1200° C. at a heating rate of 15° C. / min, keeping the temperature at 1200° C. for 5 h, and finally cooling the green body to room temperature at a rate of 5° C. / min to obtain the lightweight thermal insulating ceramic material.
[0067] The spray drying parameters in step (1) are: air inlet temperature: 200°C; air outlet temperature: 100°C; atomization pressure: 3MPa; nozzle diameter: 1mm.
[0068] Example 2
[0069] A lightweight thermal insulation ceramic material, composed of the following components by weight:
[0070] Kaolin: 35 parts;
[0071] Feldspar: 35 parts;
[0072] Hollow ceramic microspheres: 12 parts;
[0073] Alumina: 9 parts;
[0074] Composite foaming agent: 6 parts;
[0075] Nucleating agent: 0.8 parts;
[0076] Silicone wettability additive: 0.8 parts;
[0077] Coral mucus: 1.6 parts;
[0078] Polyammonium carbonate: 0.7 parts.
[0079] The composite foaming agent is CaCO3.
[0080] The nucleating agent is silicon oxide.
[0081] The silicon wettability aid is γ-aminopropyltriethoxysilane.
[0082] The present invention also provides a method for preparing a lightweight thermal insulation ceramic material, comprising the following steps:
[0083] (1) By weight, kaolin, feldspar and alumina powder were sieved through a 100-mesh sieve to remove large impurities. Then, 35 parts of the sieved kaolin, 35 parts of the sieved feldspar, 9 parts of the sieved alumina powder, 12 parts of hollow ceramic microspheres, 6 parts of a composite foaming agent, 0.8 parts of a nucleating agent, 0.8 parts of a silicon wettability aid, 1.6 parts of coral mucus and 0.7 parts of polyammonium carbonate were mixed, and 13 parts of water were added. The mixture was ball-milled at a speed of 400 r / min for 4 h to obtain a homogeneous slurry. Finally, the granulation was performed by spray drying to control the particle diameter to 2 mm.
[0084] (2) Pressing the particles obtained by spray drying in step (1) into a green body by a bidirectional pressing process at a pressure of 40 MPa; heating the green body at 90° C. for 10 h in a drying furnace to obtain a dried green body; pre-sintering the dried green body at 800° C. for 2.5 h, then heating the green body from 900° C. to 1200° C. at a heating rate of 15° C. / min, keeping the temperature at 1200° C. for 5 h, and finally cooling the green body to room temperature at a rate of 5° C. / min to obtain the lightweight thermal insulating ceramic material.
[0085] The spray drying parameters in step (1) are: air inlet temperature: 200°C; air outlet temperature: 100°C; atomization pressure: 3MPa; nozzle diameter: 1mm.
[0086] Example 3
[0087] A lightweight thermal insulation ceramic material, composed of the following components by weight:
[0088] Kaolin: 35 parts;
[0089] Feldspar: 35 parts;
[0090] Hollow ceramic microspheres: 12 parts;
[0091] Alumina: 9 parts;
[0092] Composite foaming agent: 6 parts;
[0093] Nucleating agent: 0.8 parts;
[0094] Silicone wettability additive: 0.8 parts;
[0095] Coral mucus: 1.6 parts;
[0096] Polyammonium carbonate: 0.7 parts.
[0097] The composite foaming agent is SiC.
[0098] The nucleating agent is silicon oxide.
[0099] The silicon wettability aid is γ-aminopropyltriethoxysilane.
[0100] The present invention also provides a method for preparing a lightweight thermal insulation ceramic material, comprising the following steps:
[0101] (1) By weight, kaolin, feldspar and alumina powder were sieved through a 100-mesh sieve to remove large impurities. Then, 35 parts of the sieved kaolin, 35 parts of the sieved feldspar, 9 parts of the sieved alumina powder, 12 parts of hollow ceramic microspheres, 6 parts of a composite foaming agent, 0.8 parts of a nucleating agent, 0.8 parts of a silicon wettability aid, 1.6 parts of coral mucus and 0.7 parts of polyammonium carbonate were mixed, and 13 parts of water were added. The mixture was ball-milled at a speed of 400 r / min for 4 h to obtain a homogeneous slurry. Finally, the granulation was performed by spray drying to control the particle diameter to 2 mm.
[0102] (2) Pressing the particles obtained by spray drying in step (1) into a green body by a bidirectional pressing process at a pressure of 40 MPa; heating the green body at 90° C. for 10 h in a drying furnace to obtain a dried green body; pre-sintering the dried green body at 800° C. for 2.5 h, then heating the green body from 900° C. to 1200° C. at a heating rate of 15° C. / min, keeping the temperature at 1200° C. for 5 h, and finally cooling the green body to room temperature at a rate of 5° C. / min to obtain the lightweight thermal insulating ceramic material.
[0103] The spray drying parameters in step (1) are: air inlet temperature: 200°C; air outlet temperature: 100°C; atomization pressure: 3MPa; nozzle diameter: 1mm.
[0104] Example 4
[0105] A lightweight thermal insulation ceramic material, composed of the following components by weight:
[0106] Kaolin: 35 parts;
[0107] Feldspar: 35 parts;
[0108] Hollow ceramic microspheres: 12 parts;
[0109] Alumina: 9 parts;
[0110] Composite foaming agent: 6 parts;
[0111] Silicone wettability additive: 0.8 parts;
[0112] Coral mucus: 1.6 parts;
[0113] Polyammonium carbonate: 0.7 parts.
[0114] The composite foaming agent is prepared by mixing CaCO3 and SiC in a mass ratio of 3:2.
[0115] The silicon wettability aid is γ-aminopropyltriethoxysilane.
[0116] The present invention also provides a method for preparing a lightweight thermal insulation ceramic material, comprising the following steps:
[0117] (1) By weight, kaolin, feldspar and alumina powder were sieved through a 100-mesh sieve to remove large impurities. Then, 35 parts of the sieved kaolin, 35 parts of the sieved feldspar, 9 parts of the sieved alumina powder, 12 parts of hollow ceramic microspheres, 6 parts of a composite foaming agent, 0.8 parts of a silicon wettability aid, 1.6 parts of coral mucus and 0.7 parts of polyammonium carbonate were mixed, and 13 parts of water were added. The mixture was ball-milled at a speed of 400 r / min for 4 h to obtain a homogeneous slurry. Finally, the slurry was granulated by spray drying to control the particle diameter to 2 mm.
[0118] (2) Pressing the particles obtained by spray drying in step (1) into a green body by a bidirectional pressing process at a pressure of 40 MPa; heating the green body at 90° C. for 10 h in a drying furnace to obtain a dried green body; pre-sintering the dried green body at 800° C. for 2.5 h, then heating the green body from 900° C. to 1200° C. at a heating rate of 15° C. / min, keeping the temperature at 1200° C. for 5 h, and finally cooling the green body to room temperature at a rate of 5° C. / min to obtain the lightweight thermal insulating ceramic material.
[0119] The spray drying parameters in step (1) are: air inlet temperature: 200°C; air outlet temperature: 100°C; atomization pressure: 3MPa; nozzle diameter: 1mm.
[0120] Example 5
[0121] A lightweight thermal insulation ceramic material, composed of the following components by weight:
[0122] Kaolin: 35 parts;
[0123] Feldspar: 35 parts;
[0124] Hollow ceramic microspheres: 12 parts;
[0125] Alumina: 9 parts;
[0126] Composite foaming agent: 6 parts;
[0127] Nucleating agent: 0.8 parts;
[0128] Silicone wettability additive: 0.8 parts;
[0129] Coral mucus: 1.6 parts;
[0130] Polyammonium carbonate: 0.7 parts.
[0131] The composite foaming agent is prepared by mixing CaCO3 and SiC in a mass ratio of 3:2.
[0132] The nucleating agent is silicon oxide.
[0133] The silicon wettability aid is γ-aminopropyltriethoxysilane.
[0134] The present invention also provides a method for preparing a lightweight thermal insulation ceramic material, comprising the following steps:
[0135] (1) By weight, kaolin, feldspar and alumina powder were sieved through a 100-mesh sieve to remove large particles of impurities, and then 35 parts of the sieved kaolin, 35 parts of the sieved feldspar, 9 parts of the sieved alumina powder, 12 parts of hollow ceramic microspheres, 6 parts of a composite foaming agent, 0.8 parts of a nucleating agent, 0.8 parts of a silicon wettability aid, 1.6 parts of coral mucus, and 0.7 parts of polyammonium carbonate were mixed, and 13 parts of water were added, and the mixture was ball-milled at a speed of 400 r / min for 4 h to obtain a homogeneous slurry;
[0136] (2) The homogeneous slurry obtained in step (1) is pressed into a green body by a bidirectional pressing process at a pressure of 40 MPa; the green body is heated in a drying furnace at 90°C for 10 h to obtain a dried green body; the dried green body is pre-sintered at 800°C for 2.5 h, then the temperature is increased from 900°C to 1200°C at a heating rate of 15°C / min, and the green body is kept at 1200°C for 5 h, and finally the temperature is decreased to room temperature at a rate of 5°C / min to obtain the lightweight thermal insulating ceramic material.
[0137] The spray drying parameters in step (1) are: air inlet temperature: 200°C; air outlet temperature: 100°C; atomization pressure: 3MPa; nozzle diameter: 1mm.
[0138] Comparative Example 1
[0139] A lightweight thermal insulation ceramic material, composed of the following components by weight:
[0140] Kaolin: 35 parts;
[0141] Feldspar: 35 parts;
[0142] Hollow ceramic microspheres: 12 parts;
[0143] Alumina: 9 parts;
[0144] Composite foaming agent: 6 parts;
[0145] Nucleating agent: 0.8 parts;
[0146] Silicone wettability additive: 0.8 parts;
[0147] Polyammonium carbonate: 0.7 parts.
[0148] The composite foaming agent is prepared by mixing CaCO3 and SiC in a mass ratio of 3:2.
[0149] The nucleating agent is silicon oxide.
[0150] The silicon wettability aid is γ-aminopropyltriethoxysilane.
[0151] The present invention also provides a method for preparing a lightweight thermal insulation ceramic material, comprising the following steps:
[0152] (1) By weight, kaolin, feldspar and alumina powder were sieved through a 100-mesh sieve to remove large impurities. Then, 35 parts of the sieved kaolin, 35 parts of the sieved feldspar, 9 parts of the sieved alumina powder, 12 parts of hollow ceramic microspheres, 6 parts of a composite foaming agent, 0.8 parts of a nucleating agent, 0.8 parts of a silicon wettability aid, and 0.7 parts of polyammonium carbonate were mixed, and 13 parts of water were added. The mixture was ball-milled at a speed of 400 r / min for 4 h to obtain a homogeneous slurry. Finally, the granulation was performed by spray drying to control the particle diameter to 2 mm.
[0153] (2) Pressing the particles obtained by spray drying in step (1) into a green body by a bidirectional pressing process at a pressure of 40 MPa; heating the green body at 90° C. for 10 h in a drying furnace to obtain a dried green body; pre-sintering the dried green body at 800° C. for 2.5 h, then heating the green body from 900° C. to 1200° C. at a heating rate of 15° C. / min, keeping the temperature at 1200° C. for 5 h, and finally cooling the green body to room temperature at a rate of 5° C. / min to obtain the lightweight thermal insulating ceramic material.
[0154] The spray drying parameters in step (1) are: air inlet temperature: 200°C; air outlet temperature: 100°C; atomization pressure: 3MPa; nozzle diameter: 1mm.
[0155] Comparative Example 2
[0156] A lightweight thermal insulation ceramic material, composed of the following components by weight:
[0157] Kaolin: 35 parts;
[0158] Feldspar: 35 parts;
[0159] Hollow ceramic microspheres: 12 parts;
[0160] Alumina: 9 parts;
[0161] Nucleating agent: 0.8 parts;
[0162] Silicone wettability additive: 0.8 parts;
[0163] Coral mucus: 1.6 parts;
[0164] Polyammonium carbonate: 0.7 parts.
[0165] The nucleating agent is silicon oxide.
[0166] The silicon wettability aid is γ-aminopropyltriethoxysilane.
[0167] The present invention also provides a method for preparing a lightweight thermal insulation ceramic material, comprising the following steps:
[0168] (1) By weight, kaolin, feldspar and alumina powder were sieved through a 100-mesh sieve to remove large particles of impurities. Then, 35 parts of the sieved kaolin, 35 parts of the sieved feldspar, 9 parts of the sieved alumina powder, 12 parts of hollow ceramic microbeads, 0.8 parts of a nucleating agent, 0.8 parts of a silicon wettability aid, 1.6 parts of coral mucus, and 0.7 parts of polyammonium carbonate were mixed, and 13 parts of water were added. The mixture was ball-milled at a speed of 400 r / min for 4 h to obtain a homogeneous slurry. Finally, the slurry was granulated by spray drying to control the particle diameter to 2 mm.
[0169] (2) Pressing the particles obtained by spray drying in step (1) into a green body by a bidirectional pressing process at a pressure of 40 MPa; heating the green body at 90° C. for 10 h in a drying furnace to obtain a dried green body; pre-sintering the dried green body at 800° C. for 2.5 h, then heating the green body from 900° C. to 1200° C. at a heating rate of 15° C. / min, keeping the temperature at 1200° C. for 5 h, and finally cooling the green body to room temperature at a rate of 5° C. / min to obtain the lightweight thermal insulating ceramic material.
[0170] The spray drying parameters in step (1) are: air inlet temperature: 200°C; air outlet temperature: 100°C; atomization pressure: 3MPa; nozzle diameter: 1mm.
[0171] Test Example 1
[0172] The compressive strength of the lightweight thermal insulating ceramic materials obtained in the examples and comparative examples was tested with reference to GB / T 10294-2008 “Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method”. The results are shown in Table 1.
[0173] Table 1: Thermal conductivity of lightweight insulating ceramic materials
[0174]
[0175] Test Example 2
[0176] The compressive strength of the lightweight insulating ceramic materials obtained in the examples and comparative examples were tested with reference to GB / T 5072-2023 “Test method for compressive strength of refractory materials at room temperature”. The results are shown in Table 2.
[0177] Table 2: Compressive strength of lightweight thermal insulation ceramic materials
[0178]
[0179] As can be seen from Table 1, the lightweight thermal insulation ceramic material prepared in Example 1 has the lowest thermal conductivity. Examples 2 and 3 use a single foaming agent, and their thermal conductivity is higher than that of Example 1. This shows that the use of CaCO3 and SiC composite foaming agents forms evenly distributed small pores through two-stage decomposition, which can effectively hinder the conduction of heat. Example 4 does not add a nucleating agent. After the nucleating agent is missing, the bubbles generated by the foaming agent lack uniform nucleation points, resulting in random bubble distribution, uneven pore size, and large pores or bubble aggregation areas in some areas. Large pores and bubble aggregation will reduce the thermal insulation performance of the material because these areas are prone to form "thermal bridges" and increase heat conduction. Example 5 does not use spray drying, but direct pressing. The lack of a spray drying step will lead to uneven distribution of particle sizes, and the slurry is prone to accumulation or voids during the molding process, affecting the uniformity of the pore structure. Uneven particles will lead to uneven pore size, reduced closed porosity, and poor overall thermal conductivity of the material. Therefore, the thermal conductivity of Example 5 is also higher than that of Example 1. Compared with Example 1, Comparative Example 1 lacks coral mucus, and its thermal conductivity increases. The present invention believes that this is because the coral mucus can synergize with the silicon wettability additive to improve the fluidity and formability of the slurry and make the pore structure more uniform. Comparative Example 2 does not add a composite foaming agent, and the pore size is too large, forming a thermal bridge effect, which significantly increases the thermal conductivity. Therefore, under the joint action of the composite foaming agent, nucleating agent, coral mucus and silicon wettability additive, the lightweight thermal insulation ceramic material obtained by spray drying and granulation and then pressing and sintering has the best thermal insulation performance.
[0180] In addition, as can be seen from Table 2, Example 1 also has the highest compressive strength. The present invention believes that the use of the composite foaming agent makes the pores evenly distributed and the pore wall thickness moderate, which helps to disperse the external force; spray drying improves the density uniformity of the green body and reduces the internal stress concentration; coral mucus can play a synergistic role with the silicon wettability additive to improve the fluidity and formability of the slurry and reduce the cracks inside the green body; the role of the nucleating agent is to increase the number of bubbles and the proportion of pores and improve the stability of the overall microstructure. Therefore, under the joint action of the composite foaming agent, the nucleating agent, the coral mucus and the silicon wettability additive, the lightweight thermal insulation ceramic material obtained by spray drying granulation and then pressing and sintering has the best thermal insulation performance and compressive strength.
Claims
1. A lightweight thermal insulation ceramic material, characterized in that: By mass, it is composed of the following components: Kaolin: 30-40 parts; Feldspar: 30-40 parts; Hollow ceramic microspheres: 10-15 parts; Alumina: 8-10 parts; Composite foaming agent: 5-8 parts; Nucleating agent: 0.5-1 part; Silicone wettability additive: 0.5-1 part; Coral mucus: 1-2 parts; Polyammonium carbonate: 0.5-1 part; The composite foaming agent is made of CaCO3 and SiC in a mass ratio of 3: (1-2) and has a particle size of 5-10 microns; The silicon wettability aid is at least one of sodium silicate, γ-aminopropyltriethoxysilane and methyltrimethoxysilane.
2. The lightweight thermal insulating ceramic material according to claim 1, characterized in that: The melting point of the hollow ceramic microspheres is 1300-1400°C.
3. The lightweight thermal insulating ceramic material according to claim 1, characterized in that: The nucleating agent is at least one of titanium dioxide and silicon oxide.
4. A method for preparing the lightweight thermal insulating ceramic material as claimed in claim 1, characterized in that: The following steps are involved: (1) By weight, kaolin, feldspar and alumina powder are sieved through a 100-mesh sieve to remove large impurities, and then 30-40 parts of the sieved kaolin, 30-40 parts of the sieved feldspar, 8-10 parts of the sieved alumina powder, 10-15 parts of hollow ceramic microspheres, 5-8 parts of a composite foaming agent, 0.5-1 part of a nucleating agent, 0.5-1 part of a silicon wettability aid, 1-2 parts of coral mucus, and 0.5-1 part of polyammonium carbonate are mixed, and 10-15 parts of water are added, and the mixture is ball-milled at a speed of 300-400 r / min for 3-5 hours to obtain a homogeneous slurry, and finally granulated by spray drying to control the particle diameter to 1-3 mm; (2) Pressing the particles obtained by spray drying in step (1) into a green body through a bidirectional pressing process; heating the green body in a drying furnace at 80-100°C for 8-12 hours to remove moisture and stabilize the shape of the green body, thereby obtaining a dried green body; pre-sintering the dried green body at 700-900°C for 2-3 hours, and then heating the green body from 700-900°C to 1200-1300°C at a heating rate of 10-20°C / min to avoid bubble collapse or excessive expansion; maintaining the temperature at 1200-1300°C for 4-6 hours to complete matrix densification and pore structure stabilization; and finally cooling the green body to room temperature at 5-10°C / min to avoid cracking of the green body due to thermal shock, thereby obtaining the lightweight thermal insulating ceramic material.
5. The method for preparing a lightweight thermal insulating ceramic material according to claim 4, characterized in that: The spray drying parameters of step (1) are: air inlet temperature: 180-200°C; air outlet temperature: 100-120°C; atomization pressure: 2-3 MPa; nozzle diameter: 1-1.5 mm.
Citation Information
Patent Citations
A lightweight heat-insulating ceramic product and its manufacturing method
CN105174905B
Low-temperature preparation method for lightweight heat-insulation ceramics
CN108129131A
Vitrified micro-bead heat-preservation fireproof integrated board
CN106915950A
Fireproof thermal-insulated decorative board made of pure inorganic material
CN108863404A